Two new deep-sea species of Capitella (Annelida: Capitellidae) from sunken wood in the Northeast Pacific - Magalhäes, Wagner F.; Hilliard, Justin (Zootaxa, 2022)
Natural and experimental wood falls harbor a rich and abundant macrofaunal community in the deep-sea. Two undescribed capitellids have been collected from wood species bundles deployed at 3,100 m at the “Deadwood 2” site in Monterey Bay and several other locations in the northeastern Pacific. Capitella blakei sp. nov. is a widely distributed deep-sea capitellid in the northeastern Pacific occurring from the Monterey canyon north to the Endeavour segment of the San Juan de Fuca Ridge, a range of almost 1,400 km. It belongs to a group of Capitella species having only individuals with male external characteristics, chaetigers 1–7 with notopodial and neuropodial capillaries and is readily distinguished from its congeners by the presence of a peristomium clearly separated from prostomium, deep lateral and ventral grooves, and methyl green staining pattern. Capitella multibranchiata sp. nov. is unique in the genus by the presence of branchiae on abdominal notopodial and neuropodial segments. The adult morphology of both species is described and compared to their most apparently related congeners. Our results have shown a greater diversity of deep-sea Capitella than previously known. The wide geographical distribution of C. blakei sp. nov. on wood habitats indicates that these wood falls may be functioning as ecological and evolutionary stepping-stones between the enriched sediments of vents and seeps.